The human short-chain dehydrogenase/reductase (SDR) superfamily: a bioinformatics summary. - Bray, J; Marsden, B; Oppermann, U (2009)
The short-chain dehydrogenase/reductase (SDR) superfamily represents one of the largest protein superfamilies known to date. Enzymes of this family usually catalyse NAD(P)(H) dependent reactions with a substrate spectrum ranging from polyols, retinoids, steroids and fatty acid derivatives to xenobiotics. We have currently identified 73 SDR superfamily members within the human genome. A status report of the human SDR superfamily is provided in terms of 3D structure determination, co-factor preferences, subcellular localisation and functional annotation. A simple scoring system for measuring structural and functional information (SFS score) has also been introduced to monitor the status of 5 key metrics. Currently there are 17 SDR members with an SFS score of zero indicating that almost a quarter of the human SDR superfamily lacks substantial functional annotation.